Buddhism and the Body - Kenneth W. Holloway (Brill, 2023)
Mahayana, Theravada, ancient, modern? Even at the most basic level, the diversity of Buddhism makes a comprehensive approach daunting. This book is a first step in solving the problem. In foregrounding the bodies of practitioners, a solid platform for analysing the philosophy of Buddhism begins to become apparent. Building upon somaesthetics Buddhism is seen for its ameliorative effect, which spans the range of how the mind integrates with the body. This exploration of positive effect spans from dreams to medicine. Beyond the historical side of these questions, a contemporary analysis includes its intersection with art, philosophy, and ethnography.